What Are the Support Needs of Men with Multiple Sclerosis, and Are They Being Met? - Upton, Dominic (Int J MS Care, 2015)
Background: Multiple sclerosis (MS) is a chronic, degenerative condition of the central nervous system that can lead to high levels of disability and a range of psychological and social problems. Although considerable research has been conducted on the experience of living with MS and the disease's psychosocial consequences, much of this has focused on women, with the male perspective seldom considered. It is possible, therefore, that men differ from women in how they experience MS and the type of support or interventions that meet their needs. Methods: A literature review was undertaken to identify the specific support needs of men with MS, describe current support available to men with MS, and evaluate the extent to which these needs are met by current service provision. Results: The literature reviewed suggests that the needs of men with MS are different from those of women in terms of psychological factors such as well-being and mental health and support. Conclusions: If interventions are to be evidence based, health-care professionals need to take into account the needs, desires, and capabilities of men with MS in the development of services. Further qualitative and quantitative research is required to address the gaps in the evidence base of support needs for men with MS.